Synthesis and characterization of Jatropha-based polyurethane from Jatropha-based polyol - Ahmad Hazmi, Ahmad Syafiq (2012)
A new vegetable oil-based polyol has been successfully functionalized for polyurethane fabrication. Starting with the crude jatropha oil, the double bonds are functionalized by introducing epoxy groups and followed by ring opening step to produce hydroxyl groups. This method effectively produced solvent-free epodixidized jatropha oil at rapid reaction kinetic with maximum oxirane oxygen content of 4.3%. This chemical synthesis scheme provides low viscosity and moderate functionality polyol with easier route to produce flexible film of vegetable-based polyurethane at reasonable material properties with hydroxyl number of 171 - 180 mg KOH/g, viscosity of 0.92 - 0.98 Pa.s and functionality of 5. The jatropha oil-based polyol is then reacted with aromatic diisocyanate to produce jatropha oil-based polyurethane in the present of catalyst dibutyltin dilaurate. Three distinct regions have been observed in the reactivity test of polyurethane formation corresponding to reaction of hydroxyl and isocyanate groups and branching processes. The glass transition temperature of -55 to -45 oC suggested that existence of majority flexible/soft segments and exhibited rubber-like behavior in stress-strain measurement with tensile stress at break between 2 - 6 MPa and elongation at break of 110 - 193%. Fractography evidence by SEM showed relatively flat surface with ridges and V-shaped "chevron" marking. Jatropha oil-based polyurethane is thermally stable with the onset for thermal degradation is in the range of 233 - 277 oC followed by char formation. Pseudo-plastic flow behavior with index of 0.09 - 0.24 is observed in dynamic mechanical analysis. However high amount of acid (> 0.1 mg KOH/g) in the polyol is detrimental to the branching processes with evidence of relatively low glass transition temperature (-50 oC) and mechanical strength (2 MPa).